Eksplorasi Arsitektur Masjid Agung Sang Cipta Rasa Cirebon sebagai Bahan Ajar Matematika - Thifaliani, Niken Nirvania; Lestiana, Herani Tri; Nursuprianah, Indah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Integrating cultural context into teaching and learning activities can help students understand the material. However, the development of teaching materials that integrate local cultural contexts is still not widely practiced. This study aims to (1) describe the results of exploring the architecture of the Grand Mosque of Sang Cipta Rasa Cirebon as a teaching material for mathematics, (2) determine students' responses to the mathematics teaching material resulting from the exploration of the architecture of the Grand Mosque of Sang Cipta Rasa Cirebon, and (3) determine the difference in mathematics learning outcomes before and after using the mathematics module. This study applied the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). In the architecture of the Grand Mosque of Sang Cipta Rasa, concepts of two-dimensional shapes such as triangles and quadrilaterals were found, including squares, rectangles, trapezoids, and rhombuses. The expert validation results show that the developed mathematics module is highly feasible to implement, with percentages of content, presentation, and language feasibility aspects reaching 88%, 90%, and 89% respectively. Students' responses to the mathematics module were categorized as good (71%). Paired sample t-test results show that students' learning outcomes before and after using the developed mathematics module are significantly different, with higher learning outcomes after using the mathematics module compared to before its use. Thus, the mathematics module resulting from the exploration of the architecture of the Grand Mosque of Sang Cipta Rasa Cirebon can be implemented in learning to improve mathematics learning outcomes.